A negative association between horn length and survival in a weakly dimorphic ungulate. Issue 6 (26th February 2020) - Douhard, Mathieu; Crampe, Jean‐Paul; Loison, Anne; Bonenfant, Christophe
Abstract: While all models of sexual selection assume that the development and expression of enlarged secondary sexual traits are costly, males with larger ornaments or weapons generally show greater survival or longevity. These studies have mostly been performed in species with high sexual size dimorphism, subject to intense sexual selection. Here, we examined the relationships between horn growth and several survival metrics in the weakly dimorphic Pyrenean chamois ( Rupicapra pyrenaica ). In this unhunted population living at high density, males and females were able to grow long horns without any apparent costs in terms of longevity. However, we found a negative relationship between horn growth and survival during prime age in males. This association reduces the potential evolutionary consequences of trophy hunting in male chamois. We also found that females with long horns tended to have lower survival at old ages. Our results illustrate the contrasting conclusions that may be drawn when different survival metrics are used in analyses. The ability to detect trade‐off between the expression of male secondary sexual traits and survival may depend more on environmental conditions experienced by the population than on the strength of sexual selection. Abstract : In this study, we examined correlations between horn growth and several survival metrics in an unhunted population of Pyrenean chamois. Males and females were able to grow long horns without any apparent costs in terms of longevity. However, males with long horns showed a lower survival during early adulthood than those with smaller horns.